O conhecimento sobre os recursos vegetais alimentares em bairros rurais no Vale do Paraíba, SP, Brasil - Pilla, Milena Andrea Curitiba; Amorozo, Maria Christina de Mello (FapUNIFESP (SciELO), 2009)
The objective of this study was to conduct an inventory of food plants cultivated and collected from the native and ruderal vegetation in the Atlantic Forest region by the rural population residing in the Santa Virginia Nucleus of the Serra do Mar State Park (Puruba and Guaricanga neighborhoods) and surroundings (Vargem Grande neighborhood). The 23 interviewees were sampled to meet the following criteria: originating from the rural area of the municipalities where the Nucleus is located; more than 45 years old; close familiarity with working the land. A total of 146 botanical species were identified, distributed among 43 botanical families, with the families Solanaceae and Cucurbitaceae being the most represented and basically horticultural. The Shannon-Wiener diversity index and Pielou evenness were 1.90 (base 10) and 0.95, respectively, for the group residing in the Nucleus and 1.97 and 0.92 for the population located in the area surrounding the Nucleus. The two groups of neighborhoods presented similarity regarding the food plants cited (75%), and about 17% of the plants cited are native to the Atlantic Forest. We found significant richness and variety of species cultivated in the yards and fields which serve to complement the diet, which is composed mainly of items purchased at local businesses. The rural communities studied revealed themselves to be an important germplasm conservation system for cultivated plants, with 96 ethnovarieties identified for 12 botanical species, most of which are kept in the communities.
Knowledge regarding vegetable food resources in rural neighborhoods in the Paraíba Valley, São Paulo state, Brazil
Keywords: Atlantic forest; Biodiversity; Ethnobotany; Food plants; Rural communities; Cucumis sativus; Cucurbitaceae; Magnoliophyta; Solanaceae